Metode Penetapan Mustahiq Zakat Pada Mustahiq Center Baznas Kabupaten Wonosobo - Anwar, Choerul; Handoyo, Handoyo (Program Studi Hukum Ekonomi Syariah, 2023)
This paper will analyze the method of determining mustahiq zakat through the mustahiq center at BAZNAS Wonosobo Regency. In this study the writer will use a qualitative approach with descriptive methods. The data source used is the method of determining mustahiq zakat through the mestahiq center used by the Wonosobo National Amil Zakat Agency (BAZNAS). The results of this study can be concluded that the National Amil Zakat Agency (BAZNAS) of Wonosobo Regency in determining mustahiq zakat by developing an integrated national Mustahiq database system (Mustahiq Data Center). This system is presented in an effort to sharpen the target of zakat recipients by utilizing existing poverty data in Wonosobo district.